Development of a PacBio Long-Read Sequencing Assay for High Throughput Detection of Fungicide Resistance in Zymoseptoria tritici - Samils, Berit; Andersson, Björn; Edin, Eva; Elfstrand, Malin; Rönneburg, Tilman; Bucur, Diana; Hutton, Fiona; Heick, Thies M.; Hellin, Pierre; Kildea, Steven (Frontiers in Microbiology, 2021)
Fungicide resistance has become a challenging problem in management of Septoria tritici blotch (STB), caused by Zymoseptoria tritici, the most destructive disease of winter wheat throughout western and northern Europe. To ensure the continued effectiveness of those fungicides currently used, it is essential to monitor the development and spread of such resistance in field populations of the pathogen. Since resistance to the key families of fungicides used for STB control (demethyalation inhibitors or azoles, succinate dehydrogenase inhibitors or SDHIs and Quinone outside Inhibitors or QoIs) is conferred through target-site mutations, the potential exists to monitor resistance through the molecular detection of alterations in the target site genes. As more efficient fungicides were developed and applied, the pathogen has continuously adapted through accumulating multiple target-site alterations. In order to accurately monitor these changes in field populations, it is therefore becoming increasingly important to completely sequence the targeted genes. Here we report the development of a PacBio assay that facilitates the multiplex amplification and long-read sequencing of the target gene(s) for the azole (CYP51), SDHI (Sdh B, C, and D), and QoI (cytochrome b) fungicides. The assay was developed and optimised using three Irish Z. tritici collections established in spring 2017, which capture the range of fungicide resistance present in modern European populations of Z. tritici. The sequences obtained through the PacBio assay were validated using traditional Sanger sequencing and in vitro sensitivity screenings. To further exploit the long-read and high throughput potential of PacBio sequencing, an additional nine housekeeping genes (act, BTUB, cal, cyp, EF1, GAPDH, hsp80-1, PKC, TFC1) were sequenced and used to provide comprehensive Z. tritici strain genotyping.